FACULTY PERCEPTIONS AND EXPERIENCES OF AUTONOMY REFORMS IN KAZAKHSTANI HIGHER EDUCATION INSTITUTIONS - Apergenova, Renata (Graduate School of Education, 2020)
The aim of this study was to explore faculty perceptions and experiences of autonomy reforms at three Kazakhstani public higher education institutions. Kazakhstan has taken great steps toward institutional autonomy since the first years of its independence since 1991. However, the official movement toward autonomy was announced only in 2010 (MoES, 2010), so it is a relatively new phenomenon and an ambitious reform for Kazakhstan. The term autonomy is not conceptualized on the national level yet. This influences the procedures and policies that play a role in implementing institutional autonomy. A national understanding of what autonomy means is required. Within this context, the study explored faculty individual perceptions (Vygotsky, 1986),) of academic autonomy at Kazakhstani public higher education institutions to explore their understanding of autonomy reforms. The study is focused particularly on understand faculty experiences of autonomy in terms of teaching, research, and service within the context of reforms in organizational structures and cultural values in Kazakhstani HEIs. The study adopted a qualitative approach to explore how faculty construct their understanding of academic autonomy and interpret their experiences of autonomy reforms. The research draws a distinction between two related terms, “academic autonomy” and “academic freedom.” Institutions and faculty have a different understanding of autonomy. Some faculty indicated support of education reforms focused on autonomy, although they believe they currently have sufficient academic autonomy. Other faculty believe their work should be guided by the ministry, even though they are granted academic autonomy. In a few instances, faculty rejected the concept of autonomy outright. Institutional culture is a mindset, framed by values from the Soviet system together with power structures such as policy and legislation that could resist academic autonomy reforms. Faculty mindset, including strong traditions and habits, also influences perceptions of academic autonomy. Thus, one of the key elements of the theoretical framework is a case of cultural beliefs and norms within the institutions considered through faculty perspectives. A strong governmental power structure exists in Kazakhstan with the Ministry of Education and Science wielding considerable influence. The interplay of culture and organizational structure is considered through the Mintzberg’s theory (1979) and Hierarchy cultural dimension of Knien, Greven, Bending and Brettel (2019). Based on the investigated case study, the research has practical implementation on how the autonomy has been implementing within the Hierarchical structure of Mintzberg (1979) and how it impacts on the cultural environment. Such interplay of the cultural and structural environments may cause the restriction of autonomy. Vygotsky’s theory of human cultural and biosocial development (Vygotsky, 1986, p. 54, 59) is considered as a tool that can be used in mediating autonomy reforms to manage the cultural and structural environment of HEIs. The considered theoretical framework is useful in providing the alternative perspective in implementing autonomy reforms at the state and institutional level. The research found five key factors: national overregulation, financial dependence, external pressure, lack of trust, and lack of shared understanding of the concept of autonomy, that restrict autonomy reforms.
Keywords: Type of access: Restricted; academic culture; autonomy reforms; faculty autonomy; faculty experience and perception; faculty role; freedom chaos; organizational structure; institution